Linguistic features of advertising videos created in Spanish language - Saidova Nilufar Abdusalomovna (Goodwood Publishing, 2025)
Purpose: This study aims to conduct a comprehensive linguistic analysis of Spanish-language advertising videos, focusing on phonetic, morphological, syntactic, and semantic features. It seeks to identify how linguistic strategies, stylistic devices, and cultural elements shape the effectiveness of advertising discourse. Research Methodology: The research applied advertising discourse analysis based on Cook’s framework, examining a corpus of 450 commercials broadcast in Spain, Argentina, Mexico, and other Spanish-speaking countries between 2020–2024. The materials were categorized by medium (television, social media, online platforms) and product type (food, automotive, cosmetics, banking, telecommunications, etc.). Results: The findings reveal that Spanish advertising discourse is characterized by rhythmic sound patterns, frequent use of imperative verbs, evaluative and emotional lexicon, concise sentence structures, and multimodal integration. Phonetic devices such as assonance and alliteration enhance memorability, while clitics “te” and “se” strategically influence persuasion. Cultural values—particularly family orientation and national identity—emerge as central themes, distinguishing Spanish advertising from other linguistic contexts. Conclusions: Spanish advertising discourse combines emotional appeal, cultural identity, and pragmatic linguistic tools to maximize consumer impact. The balance of multimodal features and linguistic creativity ensures high effectiveness and brand recall. Limitations: The study is limited to Spanish-speaking countries and does not compare results directly with advertisements from other languages. Contribution: This research contributes to linguistics, marketing, and translation studies by providing empirical evidence of how cultural and linguistic features interact in advertising. It also offers practical insights for international marketing strategies and Spanish language pedagogy.